ANALYSIS OF VISITOR ATTRACTION WITH THE 4A APPROACH (ATTRACTIONS, ACCESSIBILITY, AMENITIES, ANCILLARY SERVICE) IN SNOWBAY WATERPARK, TMII JAKARTA - Ardiansyah, Imam; Fortuna, Stephanie (APPS Publications, 2020)
This research aims to determine the attractiveness analysis based on 4 aspects of the tourist destination components in Snowbay Waterpark, namely Attraction, Accessibility, Amenities, Ancillaries. This research uses a descriptive approach with mix methods, which are qualitative and quantitative. This reviews the Snowbay tourism destination component as the basis for the main attraction and in improving the management of Snowbay Waterpark it is necessary to use the SWOT analysis (Strength, Weakness, Opportunity and Threath Analysis), IFAS and EFAS matrixs. Then the results based on the SWOT matrix, it can be concluded from several internal factors IFAS and EFAS external factors that Snowbay Waterpark has a strength of (1.715), weakness with a score of (1.568), opportunities with a score of (1.831, threats with a score of (1.525). Total strengths and weaknesses (3.284), and total opportunities and threats score (3.356). While the results of the SWOT diagram matrix can be concluded the difference between the internal factors of strength and weakness, which is the X axis with a horizontal line with a value (0.147), and the difference between the external opportunity and threat factors, where the Y axis is a vertical line with a value ( 0.306). The conclusion of this research can be seen from the analysis of Attraction, Accessibility, Amenity and Ancillary Service in Snowbay Waterpark still needs improvement and improvement, and the suggestion of this research i the management of Snowbay Waterpark can continue to maintain and improve existing tourist attractions, especially waterpark rides facilities, food courts because it is included in the category is not good according to respondents' answers